MOLECULAR CHARACTERIZATION OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM CLINICAL CASES IN EAST ALGERIA - Touaitia, Rahima; Bektache, Soumia; Boutefnouchet, Nafissa; Djahoudi, Abdelghani; Bachtarzi, Mohamed (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The purpose of this study is to investigate the methicillin resistance gene, and some virulence factors in methicillin-resistant Staphylococcus aureus (MRSA) isolates by polymerase chain reaction (PCR). Methods: This study has included 12 MRSA isolates. All isolates were previously identified as S. aureus by a standard microbiological procedure, and a detection of methicillin resistance was realized by phenotypic methods. Following genomic DNA extraction, the presence of gyrA, mecA, lukPV, and tst genes was analyzed by duplex PCR. All retained S. aureus species have been found to contain gyrA gene. Results: Ten stains have been found to harbor mecA gene indicating it's responsibility for methicillin resistance in those strains. Among the 12 strains, six of which were found to be Panton-Valentine leukocidine positive while none of which has tst gene encoding the toxic shock syndrome toxin. Conclusion: The pathogenesis of MRSA infections is related to the expression of a wide variety of virulence factors. Keywords: Methicillin-resistant Staphylococcus aureus, Panton-Valentine leukocidine, Toxic shock syndrome toxin 1, Multidrug resistance, mecA.